Should we spend more on fish?—How consumer beliefs about fish influence fish and meat expenditure shares. Issue 2 (13th December 2019) - Morales, Luis Emilio; Higuchi, Angie
Abstract: Health benefits derived from regular fish intake have encouraged governments to promote its consumption. However, can beliefs about fish increase expenditure on fish and reduce meat expenditure? Survey data from Modern Metropolitan Lima, Peru, indicate that female respondents were more likely to spend a bigger proportion on fish, while more educated respondents spent less on fish. Also, those with a higher household income and who eat fast food regularly were more likely to spend a bigger proportion on beef. Factors that positively influence expenditure share on fish were the belief that fish is healthy and nutritious, a preference for fish flavor and familiarity with fish. Conversely, these beliefs reduced the expenditure shares on beef and chicken. These outcomes demonstrate both the positive effect of fish consumption campaigns on fish expenditure and their negative impacts on meat expenditure, which has implications for campaigns developed by governments and the meat industry. Practical applications: Food policies and campaigns that promote regular fish consumption by highlighting its positive health benefits and nutritional content can influence the proportion that consumers spend on fish versus other sources of animal protein, beyond their effects on consumer preferences and willingness‐to‐pay for fish. However, these campaigns can result in reduced meat expenditure. These substitution effects between expenditure on related products, such as the case of fish and different types of meats, need to be considered by the authorities and the food industry, as new marketing strategies may need to be developed to increase the consumption of specific fish and meat products that have positive health and nutrition properties. In addition, food processors and retailers could introduce and promote new products in convenient formats for meal preparation to encourage consumption of fish and meat as part of a healthy diet.